Desarrollo de un sistema para medir la temperatura de gases de escape en los cilindros del motor diésel Caterpillar 3516B para el diagnóstico de inyectores. (2022)
This article seeks to provide a alternative to improve the evaluation and diagnosis in reports of low power and high temperatures of exhaust fumes on 3516B diesel engines Caterpillar, by measuring the temperature in each cylinder of the engine, with type K thermocouples, an Arduino MKR 1010 board and the visualization of data on a mobile app or on a laptop.